Water, knowledge and the environment in Asia: epistemologies, practices and locales - Baghel, Ravi; Stepan, Lea; Hill, Joseph Kelvin Walter Hill; Stephan, Lea (Routledge is an imprint of the Taylor & Francis Group, an Informa Business, 2017)
Contextualising the anthropocene : the cultures, practices and politics of water knowledge in Asia / Ravi Baghel and Lea Stepan -- Governing fisheries and marine radiation in Japan after the Fukushima nuclear accident / Leslie Mabon and Midori Kawabe -- Trans-disciplinary analysis of Australian-Indonesian monsoon epistemologies and their implications on climate change adaptation strategies / Sarah Casson -- An epistemological re-visioning of hybridity : water/lands / Kuntala Lahiri-Dutt -- Science as friend or foe? : development projects undermining farmer-managed irrigation systems in Asia's high mountain valleys / Joseph K.W. Hill -- Competing epistemologies of community-based groundwater recharge in semi-arid north Rajasthan : progress and lessons for groundwater-dependent areas / Chad Staddon and Mark Everard -- Traditional knowledge and modernization of water : the story of a desert town Jaisalmer / Chandrima Mukhopadhyay and Devika Hemalatha Devi -- The hydro-ecological self and the community of water : Anupam Mishra and the epistemological foundation of water traditions in Rajasthan / Daniel Mishori and Ricki Levi -- Epistemological undercurrents : Delhi's water crisis and the role of the urban water poor / Heather O'Leary -- Being-in-the-water, or, Socialisation through Interactions with water in the thermal baths of Taipei / Nathalie Boucher -- In the eye of the storm : water in the cross-currents of consumerism, science and tradition in India / Neeraj Vedwan -- Balinese wet rice agriculture in transition : water knowledge between a sentient ecology and the pursuit of development / Lea Stepan -- Water flows uphill to power : hydraulic development discourse in Thailand and power relations surrounding kingship and statemaking / David J.H. Blake -- Waterscapes in transition : past and present reshaping of sacred water places in Banaras / Vera Lazzaretti -- Resettling a river goddess : aspects of local culture, development and national environmental movements in conflicting discourses on Dhari Devi Temple and Srinagar Dam project in Uttarakhand, India / Frances A. Niebuhr.
Keywords: Electronic books; Konferenzschrift -- 2014 -- Heidelberg; Wassernutzung; Südostasien; Ostasien; Südasien